匿名
匿名 發問於 科學及數學其他 - 科學 · 1 十年前

physics

The gravity of the moon is only about one-sixth that of the earth's:

g earth=9.8 ms-2 g moon=1.6 ms-2

a) Try and estimate the maximum height you can reach by jumping on earth. Hence estimate your initial velocity at the moment when your feet leave the ground.

b) Assuming that you can attain the same initial velocity on the moon, estimate the maximum height you can reach if you jup on the moon.

Thank you

2 個解答

評分
  • 1 十年前
    最愛解答

    The gravity of the moon is only about one-sixth that of the earth's:

    g earth=9.8 ms-2 g moon=1.6 ms-2

    a) Try and estimate the maximum height you can reach by jumping on earth. Hence estimate your initial velocity at the moment when your feet leave the ground.

    v2 = u2 – 2gEhE

    at the maximum height,v = 0,

    such that

    02 = u2 – 2gEhE

    hE = u2 / 2gE ___(1)

    where u is initial velocity,gE = gravity of the earth

    b) Assuming that you can attain the same initial velocity on the moon, estimate the maximum height you can reach if you jump on the moon.

    gM = gravity of the moon,

    v2 = u2 – 2gMhM

    at the maximum height,v = 0,

    such that

    02 = u2 – 2gMhM

    hM = u2 / 2gM ___(2)

    (2) divide by (1)

    hE/hM = (u2 / 2gE)/(u2 / 2gM)

    hM = hE(gE/gM) = hE(6/1)

    hM = 6hE

  • 1 十年前

    The gravity of the moon is only about one-sixth that of the earth's:

    g earth=9.8 ms-2 g moon=1.6 ms-2

    a) Try and estimate the maximum height you can reach by jumping on earth. Hence estimate your initial velocity at the moment when your feet leave the ground.

    v2 = u2 – 2gEhE

    at the maximum height,v = 0,

    such that

    02 = u2 – 2gEhE

    hE = u2 / 2gE ___(1)

    where u is initial velocity,gE = gravity of the earth

    b) Assuming that you can attain the same initial velocity on the moon, estimate the maximum height you can reach if you jump on the moon.

    gM = gravity of the moon,

    v2 = u2 – 2gMhM

    at the maximum height,v = 0,

    such that

    02 = u2 – 2gMhM

    hM = u2 / 2gM ___(2)

    (2) divide by (1)

    hE/hM = (u2 / 2gE)/(u2 / 2gM)

    hM = hE(gE/gM) = hE(6/1)

    hM = 6hE

還有問題嗎?立即提問即可得到解答。